New views of humpback whale flow dynamics and oral morphology during prey engulfment. Issue 4 (14th May 2019) - Werth, Alexander J.; Kosma, Madison M.; Chenoweth, Ellen M.; Straley, Janice M.
Abstract: The rise of inexpensive, user‐friendly cameras and editing software promises to revolutionize data collection with minimal disturbance to marine mammals. Video sequences recorded by aerial drones and GoPro cameras provided close‐up views and unique perspectives of humpback whales engulfing juvenile salmon at or just below the water surface in Southeast Alaska and Prince William Sound. Although humpback feeding is famous for its flexibility, several stereotyped events were noted in the 47 lunges we analyzed. Engulfment was rapid (mean 2.07 s), and the entrance through which the tongue inverts into the ventral pouch was seen as water rushes in. Cranial elevation was a major contributor to gape, and pouch contraction sometimes began before full gape closure, with reverberating waves indicating rebounding flow of water within the expanded pouch. Expulsion of filtered water began with a small splash at the anterior of the mouth, followed by sustained excurrent flow in the mouth's central or posterior regions. Apart from a splash of rebounding water, water within the mouth was surprisingly turbulence‐free during engulfment, but submersion of the whale's head created visible surface whirlpools and vortices which may aggregate prey for subsequent engulfment.